Sclerostin and Osteocalcin: Candidate Bone-Produced Hormones - Wang, Jialiang S.; Mazur, Courtney M.; Wein, Marc N. (Frontiers in Endocrinology, 2021)
In addition to its structural role, the skeleton serves as an endocrine organ that controls mineral metabolism and energy homeostasis. Three major cell types in bone - osteoblasts, osteoclasts, and osteocytes – dynamically form and maintain bone and secrete factors with systemic activity. Osteocalcin, an osteoblast-derived factor initially described as a matrix protein that regulates bone mineralization, has been suggested to be an osteoblast-derived endocrine hormone that regulates multiple target organs including pancreas, liver, muscle, adipose, testes, and the central and peripheral nervous system. Sclerostin is predominantly produced by osteocytes, and is best known as a paracrine-acting regulator of WNT signaling and activity of osteoblasts and osteoclasts on bone surfaces. In addition to this important paracrine role for sclerostin within bone, sclerostin protein has been noted to act at a distance to regulate adipocytes, energy homeostasis, and mineral metabolism in the kidney. In this article, we aim to bring together evidence supporting an endocrine function for sclerostin and osteocalcin, and discuss recent controversies regarding the proposed role of osteocalcin outside of bone. We summarize the current state of knowledge on animal models and human physiology related to the multiple functions of these bone-derived factors. Finally, we highlight areas in which future research is expected to yield additional insights into the biology of osteocalcin and sclerostin.